1287 Improving care for refugees at a 'Bridging Hotel'. (17th August 2022) - Laurenson-Schafer, Hannah; Spence, James; Watson, Mando; Myers, Louise
Abstract : Aims: Children make up a significant proportion of the refugee and asylum seeker population in the UK and have complex health needs. There are approximately 80 'Bridging Hotels' in the UK that provide temporary accommodation and support for refugees awaiting permanent placement, including healthcare. We aimed to better understand this group's experiences of healthcare and health needs in order to improve the care provided for local refugees. Specifically, we aimed to: support families in reaching the right services, to provide feedback on the model of care delivered at this hotel, and to inform future health planning for this population and similar groups. Methods: We conducted a series of interviews with five Afghan refugee families accommodated at a large inner-city hotel using an interpreter. Families were asked about their experiences of healthcare inside and outside the hotel, their health needs prior to and since coming to the UK, and their confidence in accessing care for themselves and their children. We also spoke to other healthcare professionals, including a hospital paediatrician, specialist nurse, school nurse and health visitor, about the challenges they faced when providing care for this group. Data collected by the local council and by the onsite GP practice was reviewed. This information was fed back to key stakeholders, including local public health and GP leads, and used to develop four key plans. Results: Families had overwhelmingly positive experiences at the onsite GP. However, many struggled to access mainstream GP and 111 services due to language barriers and confusion around GP registration. Many expected medication to be given at each healthcare interaction and were deterred by the 'watch and wait' approach to minor illness in the UK. Management of long-term health conditions in secondary care was complicated in this group due to interruptions to care, delays in receiving NHS numbers and GP registration, language barriers and an unstable home environment. This led to unnecessary A&E attendances and sub-optimal care. Infectious disease was an issue in the hotel. There was an outbreak of varicella in the hotel which affected 60 children. A large proportion (70%) of children lacked immunisation plans and screening for TB was limited. 1 Mental health problems were also common. Conclusion: Addressing the needs of this population requires a 'joined up' approach between healthcare providers and must be tailored to the specific population. Four key plans are being enacted to further address the ongoing needs of this population. Refugee children with complex mental or physical health needs will be discussed at existing multidisciplinary team meetings, which connect expertise from local GPs, paediatricians, school nurses, CAMHS professionals and health visitors. To address ongoing confusion around accessing healthcare services, further in-person education sessions have been delivered with a focus on child health and immunisations. An infectious disease screening programme has been jointly developed to screen for TB and blood-borne viruses, in keeping with government guidance. 1 Further initiatives to created updated vaccination plans and immunise children is also a top priority. Reference: https://assets.publishing.service.gov.uk/government/uploads/system/uploads/attachment_data/file/1016001/ARAP_Information_for_GPs_8-Aug.pdf.